We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
52
2
avatar+22 

If \(f(x)=\dfrac{a}{x+2}\), solve for the value of \(a\) so that f(0)=f^{-1}(3a).

 

Thanks!!!

 

laughlaughlaughlaughlaughlaughlaugh

 Mar 11, 2019
 #1
avatar+99441 
+1

f(0)  =   a/2

 

To find the inverse, we have that

 

y =   a / [x + 2]

y  [ x + 2 ] = a

yx + 2y  =  a

yx =  a - 2y

x  =  [ a - 2y] / y       swap  x and y

y = [ a - 2x ] /x     =  the inverse = f-1(x)

 

So

 

f-1 (3a)  =  [ a - 2(3a) ] / [3a ]      =   [ -5a ] / 3a  =  -5/3

 

So  if f(0)  = f-1(3a).....then

 

a/ 2   =  -5/3

 

a = -10/3

 

 

cool cool cool

 Mar 11, 2019
 #2
avatar+21978 
+1

Inverse Functions

If
\(\large{\mathbf{f(x)=\dfrac{a}{x+2}}}\),

solve for the value of  \(a\) so that

\( \large{\mathbf{f(0)=f^{-1}(3a)}}\).

 

\(\begin{array}{|rcll|} \hline f\Big(f^{-1}(x) \Big) &=& x \quad | \quad x = 3a \\ f\Big(f^{-1}(3a)\Big) &=& 3a \quad | \quad f^{-1}(3a) = f(0) \\ f\Big(f(0)\Big) &=& 3a \quad | \quad f(0) = \dfrac{a}{0+2} = \dfrac{a}{2} \\ f\Big(\dfrac{a}{2}\Big) &=& 3a \quad | \quad f\Big(\dfrac{a}{2}\Big) = \dfrac{a}{\dfrac{a}{2}+2} = \dfrac{2a}{4+a} \\ \dfrac{2a}{4+a} &=& 3a \quad | \quad : a \\ \dfrac{2}{4+a} &=& 3\\ 3(4+a) &=& 2 \\ 12+3a &= 2 \\ 3a &=& -10 \\ \mathbf{a} &\mathbf{=}& \mathbf{-\dfrac{10}{3}} \\ \hline \end{array} \)

 

laugh

 Mar 11, 2019

7 Online Users